Sistem Pendukung Keputusan Pemilihan Investasi Saham Menggunakan Metode TOPSIS - Saputro, Epriligo Kiyan Danur (Jurnal Sistem Informasi Dan Informatika, 2025)
Selecting the right stock investment poses a challenge for investors as it requires an in-depth analysis of various financial criteria and investment ratios. This study aims to develop a decision support system to assist investors in selecting stocks based on criteria such as Earnings Per Share (EPS), Price to Earnings Ratio (PER), Price to Book Value (PBV), Return on Equity (ROE), Debt to Equity Ratio (DER), and Dividend Yield (DY). The system is designed using the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method, which calculates and ranks stock alternatives based on priority scores. The system development process adopts the Extreme Programming (XP) approach. System testing demonstrates that the TOPSIS method effectively delivers accurate calculations. The system provides stock recommendations based on investment criteria tailored to user preferences. The findings of this study confirm that the developed decision support system can assist investors in selecting stocks that align with their investment preferences. This system is expected to serve as a valuable tool for investors in making faster, well-informed, and data-driven investment decisions.